Arus Balik Kekuasaan Sriwijaya: Relasi Ekonomi-Politik dan Agama Jalur Perdagangan Daerah Uluan - Yadri Irwansyah (LP4MK STKIP PGRI Lubuklinggau, 2024)
ABSTRACT This research is a paper about the Backflow of Srivijaya Power: Economic-Political and Religious Relations of the Uluan Trade Route. The purpose of this research is to find out what Sriwijaya's archaeological remains are in the Uluan region and why Sriwijaya also focused on trade and religious propagation missions in the Uluan region, especially Lubuklinggau, Musi Rawas and Muratara. Efforts to answer the problems and analysis in this paper are pursued with historical methods through processes and procedures starting from heuristics, then criticizing sources and verifying relevant sources. Then after going through the process of analyzing and interpreting historical facts, the last stage is historiography. From this research, the author found that there was an economic-political and religious relationship when Sriwijaya tried to instill its hegemony and influence in the Uluan area. Sriwijaya started the mission of spreading religion as an instrument to secure its political-economic interests in the Uluan region, related to the supply of trade commodities and spices needed by Sriwijaya at that time. The conclusion of this paper is that the efforts made by Srivijaya in instilling its hegemony and influence in the Uluan area were a countercurrent to Srivijaya's power itself, which was originally the ruler of the international trade route and then had an interest in fully controlling the Uluan area which was rich in spices and Srivijaya's leading commodity at that time. As for the recommendations of this paper, in the future researchers, activists and historical writers can also focus their research and writing on the glory and influence of the Srivijaya Kingdom in the Uluan area which is still very minimal, so that the balance of information and narratives about Sriwijaya can be studied proportionally.